Zemstvo Taxes and Duties as a Component of Zemstvo Selfgovernment Financial Independence - А. І. Козаченко (Теорія і практика правознавства, 2016)
The article is aimed to analyze zemstvo legislation of the Russian Empire in the second half of the ХІХ century and practical activities of zemstvo self-government bodies to establish and collect zemstvo taxes and perform duties. Recent research and publications analysis. In the post-Soviet period, the problem of financial activities of zemstvo self-government has been studied by such domestic scientists as O.M. Holovko, V.D. Honcharenko, I.V. Ivanov, S.A. Kaluhiv, M. Lavriv. Paper objective. Zemstvo financing had to be carried out by local zemstvo assemblies and partly from the state budget, which provided financial independence of zemstvo self-government. Zemstvo taxes collection and duties performing were regulated by "Regulations on Provincial and District Zemstvo Bodies of 1864," "Regulations on Provincial and District Zemstvo Bodies of 1890" and "Temporary Regulations for Zemstvo Bodies in Cases Involving Zemstvo Duties, Public Health and Social Care of 1864". The main disadvantage of zemstvo tax legislation was the fact that it did not provide distinction of zemstvo and state income sources. The lack of such distinction became the cause of conflicts between zemstvos and local authorities. District zemstvos sought to increase a share of zemstvo budget content by cities that were situated in the district. This resulted in conflicts between zemstvo and city self-government. Paper main body. Disadvantages of zemstvo activities in the field of taxation included the fact that they did not create a perfect inventory of taxation objects; due 2 to imperfect estimation, cost of land was underestimated; zemstvos differently defined relationship between price and yield of commercial and industrial establishments. Due to the lack of taxation objects’ accounting and evaluation in 80s of the XIX century, zemstvos organized conducting of statistical studies which was aimed at census of peasants’ and landlords’ estates. The main natural duties imposed on peasants and townspeople included: 1) a dray (horse-drawn) duty - providing carts for transportation of government officials and zemstvo employees; 2) a road duty - involving peasants and townspeople to build roads. Enforcement of zemstvo duties had a number of shortcomings: abuse of power by police officials, unfair distribution of duties, distraction of farmers from economic activity, lack of incentives to perform duties. Conclusions of the research. Thus, zemstvo taxation, which was a system of independent direct taxes, shows financial independence of zemstvo self-government. Statistical studies contributed by zemstvo in the 80s of the XIX century contributed to the improvement of land taxation. Zemstvo assemblies and councils prepared a regulatory framework and gained experience on establishment and collection of zemstvo taxes and performing duties. Regulations of the 1890 provided for preservation of zemstvo’s financial independence but they limited the powers of zemstvo self-government on use of own funds and strengthened state control over financial activities of zemstvo self-government